FOTOGRAFI KOMERSIL BAGI KOMUNITAS USAHA KECIL MENENGAH SOLO SMEsCOMM - Sutriyanto Sutriyanto (Abdi Seni, 2016)
The importance of media promotion in order to improve productivity must always be carried out continuously and controlled, the high costs required to make the promotion even in a simple form and understanding of the importance of promotion is the main obstacle why the promotion was not done by many SMEs. Photography knowledge is absolutely necessary in todayâ€™s campaign creation. With photography training facility utilizing the most pocket digital camera, expected to overcome one of the sources do not cause promotion. Through the production of artworks that portray the local culture will boost the popularity of the area, while also overcoming some problems of local government. Through a sociological approach, which is conducted directly in the field is expected to know the various problems faced by Small and Medium Enterprises.Key words :Â  photography, promotion, craftman.